The Influence of Competence, Motivation, Work Environment, and Job Satisfaction on Employee Performance in the Department of Public Works and Spatial Planning of Gorontalo City - Taki, Rachmiyati; Paramata, Moh. Rolli; Suyanto, Moh. Afan (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
The purpose of this study is to determine the effect of work competence, work motivation, work environment and job satisfaction on employee performance at the Gorontalo City PUPR Office. The total population sampled in this study was 80 with data analysis techniques using multiple linear regression and hypothesis testing. The research instrument used in this study is in the form of a liktert scale. The results showed that the influence of competence, motivation, work environment and job satisfaction combined on performance was 27.8%. The remaining 72.2 (100% - 27.8%) was influenced by other factors. In other words, the variability of performance that can be explained using variables of competence, motivation, work environment and job satisfaction is 27.8%. It was concluded that simultaneously competence, work motivation and job satisfaction together have a positive and significant effect on employee performance at the Gorontalo City Public Works and Spatial Planning Office.